2020
DOI: 10.21203/rs.3.rs-38696/v1
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

WITHDRAWN: Anti-Oncogenic Activities Exhibited By Secretomes Of Mesenchymal Stem Cells Are Mediated By Modulation Of KITLG and DKK1 Genes In Glioma Stem Cells.

Abstract: Abstract Background. Cancer stem cells (CSCs) use their stemness properties such as self renewal, toxicity, plasticity, and communication with the tumor microenvironment (TME) to perpetuate their lineage and survive chemotherapy. Learning how to interrupt the self renewal ability or modulate the interaction of CSCs with the TME signaling will dramatically improve therapeutic impact on patient’s remission. Anti-tumor properties of mesenchymal stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…DKK1 is an inhibitor of the Wnt signaling pathway, which can regulate Wnt through negative feedback and participates in tumor cell proliferation, apoptosis, migration, and angiogenesis (92,93). DKK1 binds to the LRP6 co-receptor and inhibits b-catenin-dependent Wnt signaling, and the downregulation of b-catenin is crucial to human immune function (94,95). Furthermore, DKK1 can regulate immune cells and suppress immune reactions through the GSK3b/E2F1/ T-bet axis in CD8 + T cells (96,97).…”
Section: Discussionmentioning
confidence: 99%
“…DKK1 is an inhibitor of the Wnt signaling pathway, which can regulate Wnt through negative feedback and participates in tumor cell proliferation, apoptosis, migration, and angiogenesis (92,93). DKK1 binds to the LRP6 co-receptor and inhibits b-catenin-dependent Wnt signaling, and the downregulation of b-catenin is crucial to human immune function (94,95). Furthermore, DKK1 can regulate immune cells and suppress immune reactions through the GSK3b/E2F1/ T-bet axis in CD8 + T cells (96,97).…”
Section: Discussionmentioning
confidence: 99%
“…Yuzaburo Shimizu et al ( 77) conducted a prospective clinical experiment in which they discovered that bone marrow MSCs could be collected from GBM patients who had previously had chemotherapy and that bone marrow MSCs were efficient carriers of oncolytic virus. Additionally, Nazneen Aslam et al (78) suggested a possible solution for GSCs and discovered that when actively developing GSCs were treated with paracrine factors from MSCs, the prospective growth capacity and pluripotent of GSCs were disrupted. This effect was mediated by up regulation of the DKK1 gene, which in addition was mediated by up regulation of the Wnt pathway mediated by inhibition of growth factor activity and down regulation of the KITLG gene activated by growth factor and cytokine activity, thus exhibiting antitumor properties.…”
Section: Bone Marrow-derived Mscsmentioning
confidence: 99%